Complications of Liver Transplantation with Successful Treatment by Interventional Radiology Techniques - Wongwiwatchai, Jitraporn; Bejrachandra, Virin; Klungboonkrong, Vivian; Ahooja, Anucha; Boonrod, Arunnit (Srinagarind Medical Journal, 2020)
Background and Objective: Liver transplantation is a treatment option for end-stage liver disease and acute liver failure. Early detection and treatment of postoperative complications have increased survival rates after liver transplantation. The objective of this study was to evaluate efficacy of the interventional radiology procedures in treatment of liver transplant complications. Material and methods: This retrospective study included 13 patients with post liver transplantation related complications, which were treated with interventional radiology procedures from July 2013 to October 2018. Demographic data, indications for liver transplantation, type of liver transplantation, liver transplantation related complications, onset of complications, interventional radiology procedures and result of treatment were collected. Results: Between July 2013 to October 2018, 13 patients undergoing 27 procedures were identified, including venoplasty for inferior vena cava and portal vein stenosis (n=3), angioplasty and stent placement without/with thrombolysis for hepatic artery stenosis and hepatic artery thrombosis (n=3), percutaneous transhepatic biliary drainage related procedures (insertion, exchange, and irrigation) for biliary stricture (n=9) and percutaneous drainage related procedures (insertion and exchange) for intraabdominal collections (n=12). Technical and clinical success rates were 100% and 96.3%, respectively. Conclusion: Interventional radiology procedures have an important role in the management of postoperative complications of liver transplantation under non-operative and minimally invasive techniques with high technical and clinical success rates.